Translations of Ukrainian diaspora in Brazil: nation-building, ideological context and activism - Nataliia Rudnytska (Cadernos de Tradução)
The article pioneers a survey of literary translations by representatives of the Ukrainian diaspora in Brazil since WWII. The translation activity is studied within the broad historical, political, and ideological context; the research combines a socio-historical perspective with an empirical study of the translation flows and agents. Due to mass political emigration of Ukrainians in the 20th century, translation was used by emigrants to preserve and develop the Ukrainian language, literature and culture that did not have normal conditions for existence in the USSR, and to give voice to the Ukrainian writers who could not have their works published in their country. The role of literary translation in Ukrainian nation-building grew due to translators’ activism and collaboration of the diaspora in different countries as well as with translators in the Ukrainian SSR. A unique role in presenting the Ukrainian literary polysystem in its entirety to the world community belongs to the Ukrainian-born citizen of Brazil Vira Selianska.